(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The Friedmann model is considered through stereographic projection of the Friedmann-Roberson-Walker metric for open, flat and closed matter-dominated universe. A relation between redshift and number density of galaxies is derived on the platform of this metric while neglecting the effects of dark matter and dark energy. The derived relation is observed to have the potential to test the fractal-homogeneous nature of our universe based on accurate future observational data.